Influencing the willingness to pay for private labels: The role of branding - Kandapa Thanasuta (2018)
© Emerald Group Publishing Limited. Purpose - The purpose of this paper is to investigate the direct and indirect relationships between brands' marketing activities and consumers' willingness to pay (WTP) for private labels (PLs) through the effect of perceived quality in different cultural contexts. This paper also provides a broader perspective by incorporating the effect of branding strategy on such relationships. Design/methodology/approach - Thailand is the studied market. In all, 819 respondents evaluated two PLs through mall interception in a leading supermarket in Bangkok. A structural equation model is used to evaluate the relationships among the constructs. Findings - The results demonstrate that sales promotions directly and indirectly influence WTP, whereas only an indirect relationship through perceived quality exists for the similarity of PL and national-brand packaging. The strength of sales promotions and the perceived quality relationship is significantly stronger for other-name PL than for own-name one. Perceived quality contributes as the factor with the most influence on WTP. Research limitations/implications - PLs should continue to invest in package improvement to increase their perceived quality. The brand must carefully choose which promotional tools to implement because such tools have both positive and negative impacts. Promotions from other-name brands should be emphasized because they have a stronger, more positive effect on perceived quality. Originality/value - This paper's contribution is its attempt to identify the reciprocal influence of WTP on PLs, which previously has been studied only as it relates to national brands. The moderating role of branding is introduced to offer insights into the influencing factors.